1991
DOI: 10.1017/s0022377800016251
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency instability excited by a mesh grid in a double-plasma device

Abstract: Coherent low-frequency oscillations whose frequency is lower than the ion plasma frequency are generated by a mesh grid with negative d.c. bias in a double-plasma device. The frequency is inversely proportional to the one-quarter power of the grid voltage under a fixed plasma density, and is proportional to the ion plasma frequency when the grid bias is kept constant. With potential profiles near the grid, which are measured by an emissive probe, the transit time of ions is numerically calculated. The inverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The sheath instability is in many respects similar to that observed in double plasma devices [37,38,39,33,40,41]. The explanations for the instability mechanism differ widely [42,43,44].…”
Section: Discussionsupporting
confidence: 58%
“…The sheath instability is in many respects similar to that observed in double plasma devices [37,38,39,33,40,41]. The explanations for the instability mechanism differ widely [42,43,44].…”
Section: Discussionsupporting
confidence: 58%
“…The sheath instability has been experimentally observed by many groups. [7][8][9][10][11][12][13][14][15] In Fig. 1, the growth rate against the inverse of the scale length is plotted for different electric field values.…”
Section: ͑15͒mentioning
confidence: 99%
“…A different mechanism has been proposed to explain the sheath instability. For example, klystron bunching of the ions in the sheath, 15 resonant interaction of the ions due to asymmetry in the sheath potential, 11 potential relaxation instability 9 or intermittent oscillation due to the onset of chaos 16 are some of the possible mechanisms proposed to explain the instability.…”
Section: Introductionmentioning
confidence: 99%
“…Singha et al studied the influence of a magnetic field on an ion sheath [5], [6]. Chutia et al studied the low frequency instability excited by an ion sheath [7]. Pal et al observed the influence of an electron beam on an ion sheath [8].…”
Section: Introductionmentioning
confidence: 99%